Synergistic application of rhizobacteria association and fertilizer for enrichment of Pennisetum purpureum growth and phytoextraction of arsenic in engineered wetland - Rahman, Md Ekhlasur; Shamsuzzaman, S. M.; Mahmud, Khairil; Uddin, Md Kamal; Ghani, Siti Salwa Abd; Shukor, Mohd Yunus Abd; Sadeq, Buraq Musa; Chompa, Sayma Serine; Akter, Amaily; Nabayi, Abba; Halmi, Mohd Izuan Effendi Bin (Taylor and Francis Ltd., 2025)
Phytoremediation utilizing constructed wetlands (CWs) has become a logical solution to improve the quality of polluted waters by acting as a sink for different pollutants. This research explores the impact of combined application of nine-rhizobacteria consortium and NPKS (nitrogen, phosphorus, potassium, and sulfur) fertilizer on the enrichment of Pennisetum purpureum growth and phytoremediation of arsenic (As) in CWs. The study comprised control and two phytoremediation treatments with Pennisetum purpureum plants: 39 mg kg-1 As only and 2% nine-rhizobacteria consortium+0.04% NPKS fertilizer+39 mg kg-1 arsenic. Bioavailable and total As were determined by inductively coupled plasma-optical emission spectrometer. Pennisetum purpureum developed effectively in the phytoremediation treatment with 2% nine-rhizobacteria consortium+0.04% NPKS fertilizer+39 mg kg-1 arsenic application and removed 99.92% bioavailable arsenic, 99.91% total extractable arsenic, and 0.03% arsenic in the leachate of CWs till the end of the experiment. The maximum efficiency of arsenic absorption at 42 days attained 6945±69.5 mg kg−1 dry weight in the phytoremediation treatment with 2% nine-rhizobacteria association+0.04% NPKS fertilizer+39 mg kg-1 arsenic application. These results suggest that phytoremediation treatments with 2% nine-rhizobacteria association+0.04% NPKS fertilizer+39 mg kg-1 arsenic can be used at arsenic phytoremediation in anthropogenically polluted environments due to its high capability to uptake arsenic.